ANALISIS FAKTOR- FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2014-2016 - Tegar Saktiana, 16.05.62.0037; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
ABSTACT The study aims to examine the effect of Corporate Social Responsibility, Profitability, firm size, firm age and ownership on firm value. The study sample consisted of 168 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2014-2016. The sampling technique was chosen by purposive sampling. Type of data used secondary data. The method of analysis used in this study is multiple linear regression and data processing using software SPSS 23.0 for windows. The results of this study indicate Corporate Social Responsibility, firm age has negative and insignificant effect to firm value, Profitability, firm size and institusional ownership has a positive and significant effect on firm value. Keywords : Corporate Social Responsibility, profitability, firm size, firm age, institutional ownership, and Firm value